Dispositivo sostenible de paletización para el transporte y almacenamiento de mercancía (2021)
At present, when sending merchandise by land, air or sea, it must go through different processes, one of them is enlistment or packaging, it is the step that is responsible for locating the merchandise on a pallet or stowage in order to transport it from the warehouse to the vehicle that will take care of your trip according to the destination, once the merchandise is located on the pallets or pallet it has to be ordered or palletized so that the merchandise does not fall during the trip, then the protection process that is developed by means of a material called film or vinipel follows, this material only allows to join and fix the merchandise to the pallet and protect it against any type of liquid that may spill during the trip. It is very important to have a correct loading of the pallets to avoid collapsing the merchandise.